INCLUSIVE EDUCATION IMPLEMENTATION: CHALLENGES AND STRATEGIES (Modern education and development, 2025)
Inclusive education aims to ensure equal learning opportunities for all students, regardless of their physical, intellectual, social, or emotional differences. This study explores the challenges in implementing inclusive education and suggests strategies for effective integration. Using a qualitative research approach, the study examines the role of teacher training, classroom adaptation, and policy support in fostering inclusivity. The findings highlight that collaboration between educators, policymakers, and parents is crucial for the successful implementation of inclusive education.Инклюзивное образование направлено на обеспечение равных возможностей обучения для всех учащихся, независимо от их физических, интеллектуальных, социальных или эмоциональных различий. В этом исследовании изучаются проблемы внедрения инклюзивного образования и предлагаются стратегии эффективной интеграции. Используя качественный исследовательский подход, в исследовании рассматривается роль подготовки учителей, адаптации классов и политической поддержки в содействии инклюзивности. Результаты подчеркивают, что сотрудничество между педагогами, политиками и родителями имеет решающее значение для успешной реализации инклюзивного образования.